Self-Control and Social Development: Evidence from Kenya - Waliu Olawale Shittu (Arthatama: Journal of Business Management and Accounting, 2019)
The current study had aimed to examine the effects of parenting style towards low self-control and character development. Also, low self-control was examined towards character development. The moderation of genetic personality was examined between these relationships. The target population was aimed towards students of Kenya. The quantitative approach was implemented for collecting the data and PLS-SEM using SmartPLS 3.2.8 was applied for analysis. Low self-control has negatively significant effect on children character development and parenting style/practices has positively significant effect on children character development while parenting style/practices has negatively significant effect on low self-control. Parenting style/practices has positively significant effect on character development with the mediation of low self-control. The relationship of low self-control and parenting style/practices with character development have not been moderated by the students’ genetic personality typology. The outcomes of the study suggested that children's character must be built in schools or mainly focus on the early childhood education institution that must pay attention to the factors of parenting style of the child as well as their genetic personality.